Afterword: Putting Together the Anthropology of Tax and the Anthropology of Ethics. Issue 2 (1st June 2020) - Venkatesan, Soumhya
Abstract: Placing the anthropology of tax and taxation in conversation with the anthropology of ethics yields productive insights into both subfields. This is because discussions and disputations about tax and taxation reveal the ways in which people articulate and evaluate their relations with others, with the state, with 'ought' and 'is', and in terms of ownership and responsibility. They open up the complex relationship between legal obligations construed as moral and ethical understandings that are grounded in reflection and seek to articulate and enact particular understandings of the 'good' and 'right'. This afterword draws on my own research with English right-wing activists, the articles that make up this special issue, and key discussions in the anthropology of ethics.